2005
DOI: 10.1007/s10751-006-9264-y
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of amorphous FeNiZrB and FeNiCoZrB alloys

Abstract: Crystallization of amorphous precursors: Fe 31 Ni 50 Zr 7 B 12 , Fe 31 Ni 40 Co 10 Zr 7 B 12 and Fe 31 Ni 30 Co 20 Zr 7 B 12 was studied by the Mössbauer spectroscopy and X-ray diffraction. The nanocrystalline phases were formed by annealing the amorphous alloys at temperatures of 440-770°C. The crystallization temperatures were determined by DSC measurements. Addition of Co atoms into FeNiZrB alloy resulted in the formation of FeCo phase with large hyperfine field of 35 T. Formation of FeCo and (FeNiCo) 23 B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Fe, Co based nanocomposites can be engineered to exhibit excellent soft magnetic properties through averaging of the magnetocrystalline anisotropy of randomly oriented nanocrystals as described by the Herzer model. 1 Most attention has focused on Fe-rich alloys 2,3 or alloys near equiatomic Fe-Co ratios 4 due to their large saturation inductions, but Co-rich [5][6][7][8][9] and Ni-containing 10,11 alloys have been increasingly explored for technical applications and/or to study their crystallization and magnetic properties. In Co-rich Co-Fe-Nb-Si-B and Co-Fe-Zr-Si-B nanocomposite alloys, Yoshizawa et al demonstrated a large field induced anisotropy and low losses for alloys with Co:Fe ratios of roughly 9:1 to 8:2.…”
mentioning
confidence: 99%
“…Fe, Co based nanocomposites can be engineered to exhibit excellent soft magnetic properties through averaging of the magnetocrystalline anisotropy of randomly oriented nanocrystals as described by the Herzer model. 1 Most attention has focused on Fe-rich alloys 2,3 or alloys near equiatomic Fe-Co ratios 4 due to their large saturation inductions, but Co-rich [5][6][7][8][9] and Ni-containing 10,11 alloys have been increasingly explored for technical applications and/or to study their crystallization and magnetic properties. In Co-rich Co-Fe-Nb-Si-B and Co-Fe-Zr-Si-B nanocomposite alloys, Yoshizawa et al demonstrated a large field induced anisotropy and low losses for alloys with Co:Fe ratios of roughly 9:1 to 8:2.…”
mentioning
confidence: 99%